A-108 Persistent viral replication maintains the tissue reservoir during drug therapy. (March 2017) - Wolinsky, Steven
Abstract : Combinations of antiretroviral drugs usually suppress viral replication and reduce viral RNA to undetectable levels in the bloodstream in HIV-1 infection. It is unclear, however, whether treatment fully suppresses viral replication in lymphoid tissue, a key reservoir established by HIV-1 during acute infection. We examined viral sequences in lymphoid tissue and blood from 3 HIV-1-infected individuals receiving antiretroviral drug therapy. Our approach for the characterization of the viral populations was robust with respect to experimental error and stochastic effect. The evolutionary patterns and population-dynamic processes from the time-structured sequence data show a strong clock-like signal and rates consistent with HIV-1 within-host evolution, suggesting that the antiretroviral drug concentration in the lymphoid tissue is insufficient to completely block virus replication. A mathematical model explains why drug resistance does not necessarily arise under conditions where drug concentrations are insufficient to fully block virus replication. These data reveal the evolutionary and infection dynamics of the virus population within the host, indicating that HIV-1 can continue to replicate and replenish the viral reservoir despite antiretroviral drug therapy.